Decentering translation studies - Wakabayashi Judy & Rita Kothari; Wakabayashi, Judy; Kothari, Rita (New Delhi Orient BlackSwan, 2014)
Intends to foreground practices and discourses of 'translation' in several non-Western traditions. This book helps push back the geographical and conceptual boundaries of the discipline. It focuses on the multiple contexts of translation in India and encompasses translation in Korea, Japan and South Africa.
Keywords: Translating & interpreting; India; History; Indic literature; History & criticism; Languages